A qualitative study of perceptions of professionals regarding multidisciplinary memory clinics for dementia care - Jessy Fenn; Sanju George; Palayoor Benyne Jos; C. T. Sudhir Kumar (Population Medicine)
Introduction Dementia is a challenging problem across the world, with over 5 million people with dementia in India. Multidisciplinary memory clinics (MCs) are the mainstay of care for people with dementia in many countries. There is limited information about the understanding of and attitudes towards MC among health and social care professionals in India. This study aimed to identify the perceived advantages and disadvantages of a multidisciplinary memory clinic model in the care of people with dementia, and to identify the facilitators and barriers in establishing and running multidisciplinary memory clinics, as perceived by a group of specialist doctors, psychologists, and social workers.